IMPACT OF VOCATIONAL SUBJECTS ON SATISFACTION WITH THE QUALITY OF TEACHING IN SECONDARY VOCATIONAL SCHOOL - Arsenov Bojović, Venera; Trišić, Igor (The Business of Tourism, 2024)
In this research, the relationship between the teaching of professional subjects and student satisfaction with the quality of professional teaching and practical forms of teaching was examined. Special emphasis is placed on the study of the impact of educational dimensions on the quality of professional teaching. These are: the development of key competences, the use of modern teaching tools and cross-subject correlation, and the use of different teaching methods and techniques in professional teaching in secondary vocational schools. For the purposes of this research, an adapted PoS (Prism of Sustainability) model was used, which was conceived on the application of the technique of surveying students and their parents, using a written questionnaire as an instrument in the research. A total of 129 respondents (70 students and 59 parents) expressed their views on the claims that can indicate the quality of the teaching of professional subjects. In addition, the respondents evaluated the statements related to the impact of professional teaching on student satisfaction with the quality of such teaching. The collected data were processed and analyzed with the help of statistical software SPSS v.21. After examining the reliability of the scales and variables, the obtained data were presented with the help of tables. The results of the research indicate significant influences of educational dimensions on the quality of teaching professional subjects, which fully confirmed the auxiliary hypotheses. In addition, the research established that professional teaching significantly contributes to student satisfaction with the quality of teaching, thus the main hypothesis is fully accepted. The results of this research can help in the design of teaching in secondary vocational schools and in the preparation of operational and individual teaching plans.
Keywords: professional teaching, teaching quality, student competencies, satisfaction with teaching quality.